A multi-technique study of the 29–31 October 2003 geomagnetic storm effect on low latitude ionosphere over Indian region with magnetometer, ionosonde, and GPS observations - Panda, Sampad Kumar; Gedam, Shirish S.; Rajaram, G.; Sripathi, S.; Pant, Tarun Kumar; Das, Rupesh M. (My University, 2014)
The present study demonstrates the ionospheric response to the extreme geomagnetic storms during 29–31 Oct 2003 (the Halloween storm), in the low latitude anomaly Indian region, based on multi-instrument measurements namely magnetometer, ionosonde, and GPS observations. Unlike earlier reports, we have suitably chosen the best quiet days (CQ-Days) amongst 10 international quiet days (Q-Days), on the basis of equatorial electrojet strength and pattern, that drives the distribution of plasma over the low latitude. We stress that arbitrarily selecting the Control/Q-Days may lead to erroneous interpretations and will not yield a clearer understanding of the equatorial electrodynamics. Our analysis confirms the anomalous increase in TEC at all stations on 29 Oct 2003 and suppressed TEC across anomaly crest latitudes during 30–31 Oct 2003. The sharp transition in h’F is noticed during the progressive period of the storm, though it was relatively lower at the equator. The respective foF2 remained subordinate at Trivandrum. However, we did not notice such foF2 changes at Delhi. Observations at various latitudes confirm the maximum positive deviation of TEC at mid-latitude POL2 (140 %), followed by the low latitude Jodhpur (108 %), and the rest of the stations showing relatively lower enhancements with deviations ranging between 60–90 %. However, at Ahmedabad, the lowest divergence from the mean CQ-Days, attribute the typical quiet day formation of crest at this latitude. Although the results are well agreeing with earlier reports, miniature differences is noticeable due to our way of choosing the best reference days in the analysis.
Keywords: Geomagnetic storm; Equatorial electrojet strength; Ionosphere; Total electron content; Equatorial ionization anomaly